18.5k views
4 votes
(15 Points)

Find the derivative of each of the following (inverse function)

f(x) = x^2 arctan(x)

f(x) = xarcsin(1-x^2)

User Palimondo
by
6.0k points

1 Answer

4 votes

ANSWER 1



Note that,



f(u)=tan^(-1)(u)


is the same as



f(u)=arctan(u)



We apply the product rule.



f(x)=x^2tan^(-1)(x)


So we keep the second function and differentiate the first,plus we keep the first function and differentiate the second.



f'(x)=(x^2)'tan^(-1)(x)+x^2(tan^(-1)(x))'



Recall that,

If


f(u)=tan^(-1)(u)



Then,


f'(u)=(1)/(1+u^2)} * u'


This implies that,


f'(x)=2xtan^(-1)(x)+(x^2)/(x^2+1)



ANSWER 2


We apply the product rule and the chain rules of differentiation here.




f(x)=xsin^(-1)(1-x^2)





f'(x)=x'sin^(-1)(1-x^2)+x(sin^(-1)(1-x^2))'



Recall that,

If


f(u)=sin^(-1)(u)



Then,


f'(u)=(1)/(√(1-u^2)) * u'



This implies that,



f'(x)=sin^(-1)(1-x^2)+x * (1)/(√(1-(1-x^2)^2))* (-2x)



f'(x)=sin^(-1)(1-x^2)-(2x^2)/(√(1-(1-2x^2+x^4)))



f'(x)=sin^(-1)(1-x^2)-(2x^2)/(√(1-1+2x^2-x^4))




f'(x)=sin^(-1)(1-x^2)-(2x^2)/(√(2x^2-x^4))





User Clafouti
by
6.3k points